Effect of health belief model-based training and social support on the physical activity of overweight middle-aged women: a randomized controlled trial - Faghih, Masoumeh; Kaveh, Mohammad Hossein; Nazari, Mahin; Khademi, Khadijeh; Hasanzadeh, Jafar (Frontiers in Public Health, 2024)
Introduction The highest incidence of overweight among adults is found among women, predominantly middle-aged women. While it has been demonstrated that being overweight increases mortality by compromising physical and mental health, it also imposes substantial costs on the healthcare system. Lack of physical activity is a primary contributing factor to becoming overweight. The majority of inactive adults are women, particularly middle-aged women. Consequently, this study investigated the training program for overweight women based on the health belief model (HBM) and social support approach. Methods A randomized, controlled trial involving 73 overweight middle-aged women (control group: 37, intervention group: 36) was conducted using simple random sampling. The intervention group participated in six 120-min sessions per week for 6 weeks of a training program based on HBM and social support through physical activity, group discussion, role play, and media. Data were collected using the Physical Activity Questionnaire (IPAQ), Bandura’s Exercise Self-Efficacy Scale (Bandura’s ESE), and a researcher-made questionnaire before and 4 weeks after the training. The collected data were analyzed using descriptive and inferential statistics via SPSS 27 software. p-values <0.05 were considered statistically significant. Results A training program based on HBM and social support led to improved perceived benefits (p < 0.001), cues to action (p = 0.03), and self-efficacy (p < 0.001) of physical activity; decreased perceived barriers (p = 0.001); increased social support (p = 0.001); and increased physical activity (p < 0.001). In addition, the BMI of the intervention group decreased after the training program (p = 0.01). Conclusion The findings of the study demonstrate the efficacy of the training program based on HBM and the social support approach in improving social support and physical activity of women. In addition, the study evaluates the long-term outcome in populations with varying social, economic, and cultural standings. Clinical Trials Registration https://clinicaltrials.gov/, (IRCT201706236261N17).